Mind the gap. The role of suppression, purges, and rejection in sports history and sports historiography. An Introduction - Arnd Krüger (Universidad Politécnica de Madrid, 2023)
Forgetting is often considered a problem of old age. It is seen as a sign of weakness, of individual frailty. Whoever uses oral history is fully aware of the problem that even an eyewitness for certain events at a certain period will have forgotten a lot or may even falsely remember something that took place in a different context. This is perfectly normal, although sometimes the historian might think that the person does not want to be remembered. As one can see in the aftermath of dictatorial government not all forgetting really means forgetting. Often the eyewitness just prefers to keep silent to avoid being drawn into a case he or she has to be careful to talk about. Apart from such individual cases of forgetting there are the collective ones. In recent times the renaming of streets, the topping of monuments, and the restitution of artifacts from museums gathered there in colonial times to their original owners or their heirs have led to considerable discussions about the blind spots in one's own history.